The First Computers Were Human. - Thompson, Clive (Smithsonian, 2019)
The article examines the contributions of women mathematicians in the development of computing technology. It discusses the use of "human computers," a term for the individuals who made the calculations used in fields such as astronomy, space travel, and military science.